Evaluation of the Performance of Silicon Solar Cell with Fresnel Lens as Photovoltaic Solar Concentrator - Obaid, Ali Hussien; Mahdi, Emad Jaleel; Muslem, Assma Hassan; Jafer , Ammar Noori; Abed, Salah Subhi; Khuder , Tariq Yasseen (Iraqi Journal of Science, 2021)
In this paper, the performance of a silicon cell with a Fresnel lens (FL) for building a solar photovoltaic concentrator system was evaluated; the solar concentrator is a Fresnel lens, which is a point concentrator made of polymethyl-methacrylate (PMMA) as a thin lens for the optics system.As the radiation from the sun on the solar cell is concentrated to the levels of solar radiation of 750, 1300, 1930, 2600, 4250, 7250, and 10500) W/m2, the work was conducted at the midday in summer weather conditions, with ambient temperatures ranging 40-45 °C. The evaluation was performed in three cases; each case was conducted in succession. The performance of the cell was evaluated first without a cooling system, and then it was evaluated using the heat-sink (phenolic (pcb) printed circuit boards type). Finally, the fan with the heat-sink was used as a cooling system, which was more effective in dissipating the heat generated in the solar cell. The evaluation, based on the current and voltage (I-V) results with cell temperature, showed the following efficiency values for the abovementioned three cases, respectively:(6.91 ,7.76 ,6.65 ,7.77 ,6.27 ,4.74 ,3.37 ) %, (7.41 , 9.21 , 7.5 , 8.31 , 9.71 ,7.53 ,4.72 ) %, and (7.63 ,9.34 , 7.57, 8.37 , 10.2 ,7.75, 4.7) %.